AWARENESS OF INFORMATION TECHNOLOGY AND ITS RELATIONSHIP TO SPORTS CULTURE AMONG STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCE - Asist. Prof. Dr. Kahlan Ramadan Salih (Galaxy International Interdisciplinary Research Journal, 2023)
By looking at the levels of electronic students and their sports culture, we found that there is an urgent need to study them and put the necessary treatment, since awareness of information technology and sports culture have the real benefit in solving problems and finding solutions for students.